Local Good Governance Sustainability: Roles of Civil Society in Surakarta City, Indonesia - TEGUH YUWONO (Jurnal Studi Pemerintahan, 2016)
Civil society role is often seen as less powerful agent in forming or maintaininggood governance than two dominant agents (state and private actors). This research is intended to have knowledge whether civil society can play importantroles in forming and maintaining local good governance in Surakarta City, Indonesia. The civil society (both formally and informally associations or persons) in Surakarta city plays very pivotal roles in six sustainable elements, namely (1) by influencing policy analysis and advocacy; (2) by controlling regulations; (3) by monitoring local government actions and behavior of staff officials; (4) by enabling citizens to identify and articulate their values, beliefs, civic norms and democratic practices; (5) by mobilizing vulnerable and marginalized masses to participate more fully in politics and public affairs and finally (6) by establishing participatory development work to improve their own better life. Interestingly, there are two new factors found in the research in determining the success of sustainability of local good governance practices in Surakarta, namely informal networking or communication and spirit of togetherness. The existence of civil society (especially the informal one) in Surakarta City is a strong pillar for sustainable local good governance practices. Maintaining this strong civil society role will make it possible to guarantee the future of the good governance in Surakarta City, Indonesia.